Ecotourism Potential: A Bibliometric Review - Shanshan SHI; Mi LI; Jianchao XI (Chinese Journal of Urban and Environmental Studies, 2023)
Ecotourism potential is a fundamental research effort needed to promote sustainable regional tourism development, and scholars have paid greater attention to it in recent years, which has led to an increase in the publication of literature on this important and widely recognized topic. However, there is still no clear picture of the development direction of research on ecotourism potential. To address this issue, this study attempts to provide a comprehensive analysis of the existing research state in this field. This paper presents a more detailed review of ecotourism potential, a bibliometric analysis of 949 articles selected from 1,027 publications retrieved from the Web of Science Core Collection database, and a systematic descriptive and network analysis of the bibliometric data using the Biblioshiny tool. Here are some interesting findings: (1) research on the ecotourism potential in the academy started in 1992, with a rapid growth in the number of publications after 2013, with an overall interdisciplinary character and the emergence of a research community represented by Milcu, Balmford, Gallagher, and others; (2) ecotourism, conservation, tourism, management, and biodiversity are high-frequency keywords in this field, revealing the main research directions; (3) the development and evolution of research focus are mainly on three aspects: wildlife and biodiversity conservation, nature-based tourism and environmental values, and the modes and contributions of community participation. Future research should focus on the scientific references of ecotourism potential for promoting regional sustainable development. This paper sheds some light on the comprehensive bibliometric studies on ecotourism potential and improves our understanding of the evolution of this academic discourse theme over the last three decades.